PENGARUH MEDIA AUDIO VISUAL TERHADAP MINAT SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI KELAS V SD NEGERI 066656 MEDAN TAHUN AJARAN 2024 - Pardede, Eni Yusnita; Mariani, Mariani; Sitompul, Ruth Sahanaya; Syaputri, Marsanda (Universitas Quality, 2025)
Every human being in this world really needs education. Education can determine the development of a country. Education has a very decisive role for the development and realization of the individual, especially for the development of the Nation and State. Every individual has the desire to connect with something in the environment. If there is something that gives him pleasure, then he will be interested in that something. The criteria for the success of student activities in this research are said to be effective if at least 65% of students are actively involved in learning, from the first meeting that is 69% in the very good category, so The overall average percentage obtained was 75% in the good category. This can be seen from the percentage of students who attended teaching and learning activities during the meeting which was 100%, the percentage of students who took part in the teaching and learning activity process until completion was 100%, the percentage of students who walked around in class was 50%, the percentage of students who paid attention to the material was 50 %, students who were able to answer questions asked by the teacher about the material being studied were 85%, students who asked questions about material that had not been understood during the teaching and learning process were 42%, students who were able to explain concepts that had been created in their own words, namely 87%, and students who did the assignments were 100%. So it can be concluded that the learning process is increased or influenced by the presence of audio-visual learning media in the Physical Education subject for class students at SD Negeri 066656 Medan.Keywords: Audio Visual, Interest, Physical Fitness